Introduction: Covid‐19 and the conditions and struggles of agrarian classes of labour. (17th June 2021) - Pattenden, Jonathan; Campling, Liam; Castañón Ballivián, Enrique; Gras, Carla; Lerche, Jens; O'Laughlin, Bridget; Oya, Carlos; Pérez‐Niño, Helena; Sinha, Shreya
Abstract: Covid‐19 generated a crisis in capitalism, but not of capitalism. Capitalism reproduces itself in crisis and in ways that have significant but uneven impacts on the conditions and struggles of agrarian classes of labour. This article explores preliminary studies of how Covid‐19 has affected agrarian social formations in Africa, Asia and Latin America and the farmers, petty commodity producers, labourers and agribusinesses who populate them. It considers some of the implications for wage‐labour, agriculture, accumulation and social reproduction including care work. And it briefly considers Covid‐19's political impacts—in terms of the role of the state and possibilities for challenging capitalism, its violence and its ecological crisis.